Komorbid Kardiovaskular dan Gastrointestinal pada Coronavirus Disease 2019 (COVID-19) - Emmanuella E. N. A Somalinggi; Frans E. N. Wantania; Bradley J. Waleleng (Universitas Sam Ratulangi, 2023)
Abstract: COVID-19 patients have various clinical characteristics. Patients who come with co-morbidities are more at risk of experiencing more severe symptoms and higher risk of death. This study aimed to obtain cardiovascular and gastrointestinal comorbidities of coronavirus disease-2019 (COVID-19). This was a literature review study. The literature search was performed by using ScienceDirect, PubMed and Clinical key databases with “Comorbid AND Cardiovascular AND COVID-19” and “Comorbid AND Gastrointestinal AND COVID-19” for the keywords. After searching and filtering the literatures based on inclusion and exclusion criteria, finally 10 literatures were determined to be reviewed. The ten literature reviews showed that COVID-19 patients had cardiovascular comorbidities including hypertension, coronary heart disease (CHD), heart failure, and atrial fibrillation. Gastrointestinal comorbidities found include chronic gastritis, peptic ulcer, gastroesophageal reflux disease (GERD), inflammatory bowel disease (IBD), irritable bowel disease, diverticular disease, gastrointestinal tumors and polyps. In conclusion, patients with COVID-19 have varieties of comorbidities, and the most common one is hypertension and GERD. Keywords: cardiovascular comorbidity; gastrointestinal comorbidity; COVID-19 Abstrak: Pasien COVID-19 memiliki karakteristik klinis yang beragam. Pasien dengan penyakit penyerta lebih berisiko mengalami gejala yang lebih berat dan risiko kematian lebih tinggi. Penelitian ini bertujuan untuk mengetahui komorbid kardiovaskular dan gastrointestinal dari coronavirus disease-2019 (COVID-19). Penelitian dilakukan menggunakan metode literature review. Pencarian literatur dilakukan pada tiga database yaitu PubMed, ScienceDirect dan ClinicalKey dengan kata kunci “Comorbid AND Cardiovascular AND COVID-19” serta “Comorbid AND Gastrointestinal AND COVID-19”. Setelah melalui proses pencarian dan penyaringan literatur berdasarkan kriteria inklusi dan ekslusi, akhirnya ditetapkan 10 literatur untuk ditelaah. Hasilnya sebanyak sepuluh tinjauan literatur menunjukkan pasien COVID-19 memiliki komorbid kardiovaskular antara lain hipertensi, penyakit jantung koroner (PJK), gagal jantung, dan fibrilasi atrial. Komorbid gastrointestinal yang ditemukan antara lain gastritis kronik, ulkus peptikum, gastroesophageal reflux disease (GERD), inflammatory bowel disease (IBD), irritable bowel disease, diverticular disease, tumor dan polip saluran cerna. Simpulan penelitian ini ialah pasien dengan COVID-19 memiliki berbagai jenis komorbid, dan yang terutama ialah hipertensi dan GERD. Kata kunci: komorbid kardiovaskular; komorbid gastrointestinal; COVID-19